2012
DOI: 10.1111/ene.12060
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke antiplatelet therapy and early prognosis in stroke patients: the Dijon Stroke Registry

Abstract: APT before stroke was associated with less severe handicap at discharge, with no significant protective effect for mortality at 1 month except in patients with cardioembolic stroke. No protective effect of APT was observed for mortality at 1 year. Further studies are needed to understand the mechanisms underlying the distinct effects of prior APT observed across the ischaemic stroke subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Some data suggests that pre-stroke antiplatelet use is associated with less severe ischemic stroke and less infarct volume (23,24), with other studies demonstrating that pre-stroke anti-platelet therapy has no impact on stroke outcome (25,26). One population-based study reported that the better prognosis seen in patients with pre-stroke antiplatelet therapy was not replicated in patients with cardioembolic stroke (27). Few data exist regarding the relationship between antiplatelet therapy and stroke outcome in patients with non-valvular AF.…”
Section: Discussionmentioning
confidence: 99%
“…Some data suggests that pre-stroke antiplatelet use is associated with less severe ischemic stroke and less infarct volume (23,24), with other studies demonstrating that pre-stroke anti-platelet therapy has no impact on stroke outcome (25,26). One population-based study reported that the better prognosis seen in patients with pre-stroke antiplatelet therapy was not replicated in patients with cardioembolic stroke (27). Few data exist regarding the relationship between antiplatelet therapy and stroke outcome in patients with non-valvular AF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of premorbid AT itself decreasing the initial stroke severity was observed from previous reports. 19 Reducing Abbreviations: AT, antiplatelet therapy; OAC, optimal anticoagulation; SOAC, suboptimal anticoagulation. Results are expressed as number (% raw) [standardized residual relative to control group].…”
Section: Discussionmentioning
confidence: 99%
“…34 There is no evidence that combining aspirin with other antiplatelet drugs improves stroke clinical outcomes compared to aspirin alone. Continued previous population-based study.…”
mentioning
confidence: 99%